Treatment of Sewage Sludge Using Anaerobic Digestion in Malaysia: Current State and Challenges - Hanum, Farida; Yuan, Lee Chang; Kamahara, Hirotsugu; Aziz, Hamidi Abdul; Atsuta, Yoichi; Yamada, Takeshi; Daimon, Hiroyuki (Frontiers in Energy Research, 2019)
Anaerobic digestion is widely considered as an environmentally friendly technology for various organic waste including sewage sludge. Although the implementation of anaerobic digestion as an alternative treatment method for sewage sludge can be seen in many countries, its status in Malaysia is not clear. This study reviewed the current state of sewage sludge treatment in Malaysia and discussed the challenges to promote anaerobic digestion in sewage sludge treatment. Other than the common constraints faced, namely technical, political and economic, the characteristics of sewage sludge in Malaysia are considered to be a factor regarding feasibility. Anaerobic co-digestion is the simultaneous anaerobic digestion of two or more substrates which is a promising possible option to overcome the disadvantages of mono-digestion, and improve the economic viability due to higher methane production. There are a variety of biomasses as co-substrates in Malaysia. However, the anaerobic co-digestion of food waste and sewage sludge might be the most feasible method to overcome such constraints. Adding food waste as co-substrate is suggested as the possible approach to not only improve the process's performance but also help to handle the increasing volume of food waste in Malaysia. This study aims to highlight the potential as well as to provide a starting point for further studies regarding the treatment of sewage sludge using anaerobic digestion in Malaysia.